2009
DOI: 10.1093/treephys/tpp084
|View full text |Cite
|
Sign up to set email alerts
|

Plastic responses of Abies pinsapo xylogenesis to drought and competition

Abstract: Radial growth and xylogenesis were studied to investigate the influence of climate variability and intraspecific competition on secondary growth in Abies pinsapo Boiss., a relic Mediterranean fir. We monitored the responses to three thinning treatments (unthinned control -C-, 30% -T30- and 60% -T60- of basal area removed) to test the hypothesis that they may improve the adaptation capacity of tree growth to climatic stress. We also assessed whether xylogenesis was differentially affected by tree-to-tree compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
84
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 48 publications
16
84
0
Order By: Relevance
“…Deterioration of growth conditions will arise for many Mediterranean species if heat and water stress are intensified (Andreu et al 2007). As Linares et al (2009) reported, drought stress is probably the main reason for the current growth decline of coniferous woodlands in southern Europe.…”
Section: Introductionmentioning
confidence: 79%
“…Deterioration of growth conditions will arise for many Mediterranean species if heat and water stress are intensified (Andreu et al 2007). As Linares et al (2009) reported, drought stress is probably the main reason for the current growth decline of coniferous woodlands in southern Europe.…”
Section: Introductionmentioning
confidence: 79%
“…During spring and autumn, and sometimes in summer, foggy and rainy days were frequent, which impeded the use of equipment in the field; otherwise, during winter, the temperatures were usually low and the study area was sometimes covered by snow [19]. In addition, the inaccessibility of the study sites necessitated the transport of the sampling devices by mules.…”
Section: Ecophysiological Variablesmentioning
confidence: 99%
“…Nonetheless, trees located at the lower elevation (1200 m) exhibited earlier symptoms of water stress, while trees located at 1550 m showed systematically higher values of stomatal conductance, as well as improved daily-scale recovery of xylem water potential and growth [11]. Regardless, both populations showed a seasonal response to increasing drought, similar to that of typical Mediterranean species, with spring maximums and low summer stomatal conductance values [19,[30][31][32].…”
Section: 1drought-avoidance Matters In a Pinsapomentioning
confidence: 99%
See 2 more Smart Citations